2002
DOI: 10.1023/a:1023844626572
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Many proteins undergo small side chain or even backbone movements on binding of different ligands into the same protein structure. This is known as induced fit and is potentially problematic for virtual screening of databases against protein targets. In this report we investigate the limits of the rigid protein approximation used by the docking program, GOLD, through cross-docking using protein structures of influenza neuraminidase. Neuraminidase is known to exhibit small but significant induced fit effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…[1824] Such conformational changes may range from small-scale side-chain rearrangement to large-scale loop movement or domain shifts. [21, 2529] Hence, it is significantly difficult to develop an unambiguous structural model of the binding pockets that can be used in computational docking studies. [22, 3035] The effect of induced fit becomes more crucial for binding sites interacting with peptides due to higher number of conformational degrees of freedom of the ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1824] Such conformational changes may range from small-scale side-chain rearrangement to large-scale loop movement or domain shifts. [21, 2529] Hence, it is significantly difficult to develop an unambiguous structural model of the binding pockets that can be used in computational docking studies. [22, 3035] The effect of induced fit becomes more crucial for binding sites interacting with peptides due to higher number of conformational degrees of freedom of the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been undertaken to account for the structural flexibility in predicting the active conformation of the binding sites[21, 25, 3654], including building of databases of experimental structures of the protein complexes with small molecule and peptide ligands. [7, 5561] Comparison of multiple crystal structures of a given protein bound to various ligands can reveal the conformational space that needs to be considered to obtain a correct definition of the binding pocket.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown similar results - the addition of more conformers can degrade performance. 12, 1416, 8486 While ensemble docking studies, ours included, consistently highlight the importance of incorporating multiple protein conformations in VS experiments, that performance does not necessarily scale with ensemble size. Clearly, even though protein kinases may adopt multiple conformations, it appears that only a small number of conformations (1–4) are important for ligand binding, at least in the context of ensemble docking.…”
Section: Discussionmentioning
confidence: 96%
“…We tested the virtual screening results against the five target proteins: 1) herpes simplex virus type 1 thymidine kinase (TK) [29] PDB identification (ID): lkim, 2) human estrogen receptor alpha (ER α ) [22,30] PDB ID: 3ert, 3) human estrogen receptor alpha (ER α ) PDB ID: lgwr, 4) human dihydrofolate reductase (hDHFR) [31,32] PDB ID: lhfr, and 5) tern n9 influenza virus neuraminidase (NA) [33,34] PDB ID: lmwe.…”
Section: Methodsmentioning
confidence: 99%